Space Cat - Doug Cushman (New York, NY, United States HarperCollins Publishers Inc, 2006)
pace Cat and his trusty robot, Earl, are forced to land their rocket on a strange planet. Space Cat has to find more fuel to get home. Will he ever blastoff again?
Keywords: Level Reader -- Level Reader